Pengaruh Resolusi 3D CAD STL Pada Kualitas Geometri dan Dimensi (G&D) Produk Pola Cor 3D Printer - Muhammad Munadi; Hamid Abdillah (P3M Politeknik Negeri Cilacap, 2020)
3D printer is a rapid prototyping technology that has developed rapidly in this decade. 3D printers use STL files derived from 3D CAD drawings as input data for the processing. The purpose of this study is to determine the effect of the resolution of the STL file used on the quality of the geometry and dimensions of the product produced. This research was conducted by using 2 types of STL file resolution created with Autodesk Inventor. The results of this study are that there is an influence of the resolution of the STL file used on the quality of the geometry and dimensions of the product being made. the quality of the product geometry has different geometric shapes in the radius. Whereas in the aspect of the product dimension obtained a product dimension accuracy of 0.02 sampai 0.8 mm.